Tuntutan Penghentian Pembangunan Jalur Pipa Gas Nord Stream 2 antara Rusia – Jerman oleh Uni Eropa - Tendy; Gustia, Raysha Rahma; Yuniarti (Journal Social Politica, 2025)
Nord Stream 2 Project is a pipeline development project proposed by Russia and Germany which was agreed upon in June of 2015. The project received objections from member countries of the European Union (EU) and demand for termination on the 18th of December, 2015 by the EU. This study aimed to explain the reasons for the European Union’s demand to terminate the construction of Nord Stream 2 pipeline in 2015. Richard C. Snyder’s decision-making theory was used as the theoretical basis in this study.The result of this study displayed the causes of the termination of the Nord Stream 2 pipeline construction, which was influenced by both internal and external factors. The EU’s common values, the effect it had on EU internal market, and environment security concerns were found to be the internal factors. On the other hand, the annexation of Crimea by Russia was considered as a violation of the self determination and democracy.